PENINGKATAN KUALITAS PEMASAKAN MIE TELUR REBUS DENGAN PENGGUNAAN KAPPA KARAGINAN - Widjajaseputra, Anna Ingani; Tanjung, Dwiana; Frida, Frida (Widya Mandala Surabaya Catholic University, 2004)
Noodle has an important role in people's diet especially in Asia region. The usage of eggs to the dough enhances the formation of a cohesive network, thus improve the cooking quality of the product. One of the problems of egg-noodle is the eating quality during prolonged cooking. Its structure can breakdown easily for longer cooking. This research studied the effect of carrageenan's usage in cooked egg noodles to strengthen its structure during cooking. This research used complete randomized design with single factor, the proportion of flour and carrageenan. The experiment was done in 3 replications and the parameters which were analyzed : moisture content, water absorption capability, extensibility, and cooking loss. The result showed that the effect of carrageenan can strengthen product's structure. Using 0,5 % - 2,5% kappa carrageenan can improve the cooking quality in 5 minutes over cooking treatment.